2001
DOI: 10.1002/1615-9861(200110)1:10<1233::aid-prot1233>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics for studying cancer cells and the development of chemoresistance

Abstract: Extensive studies during the last decades have identified several mechanisms through which cells escape the cytotoxic effects of a variety of chemotherapeutic drugs. One type of drug resistance is called multidrug resistance (MDR), because selection with one anticancer drug leads to cross-resistance with a wide range of other drugs. These MDR cells express frequently plasma transport proteins like p-glycoprotein. But cellular resistance to chemotherapy is multifactorial and may be affected by the cell cycle st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 98 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…A number of differential protein expression studies of drug-resistant cancers have also been carried out (for a review, see Ref. 51), but again the roles of most of the proteins identified by these studies in resistance remain unclear. In one study, the protein MGr1-Ag was found to be overexpressed in multidrug-resistant gastric cancer cells.…”
Section: Fig 4 Comparison Of Protein Profiles and Maldi-tof Identifmentioning
confidence: 99%
“…A number of differential protein expression studies of drug-resistant cancers have also been carried out (for a review, see Ref. 51), but again the roles of most of the proteins identified by these studies in resistance remain unclear. In one study, the protein MGr1-Ag was found to be overexpressed in multidrug-resistant gastric cancer cells.…”
Section: Fig 4 Comparison Of Protein Profiles and Maldi-tof Identifmentioning
confidence: 99%
“…Modalities that allow realtime, in-vivo analysis of transporter function may prove useful in determining in-situ activity of the resistance mechanism in question (Luker et al 1997). Finally, the advent of proteomics and other genome-scale approaches for the global analysis of cancer biology may accelerate the identification and characterization of previously unrealized mechanisms responsible for tumour drug resistance (Hutter & Sinha 2001).…”
Section: Current Researchmentioning
confidence: 99%
“…The translational research can provide the new tools for the clinicians to be used in patients and for assessment of their impact. Recent proteomics studies in pancreatic cancer have identified proteins differentially regulated in cancer samples and have led to the discovery of several candidate biomarkers (4)(5)(6)(7)(8). Currently one pilot study has reported of establishing circulating tumor cells as a biomarker for pancreatic cancer (9).…”
mentioning
confidence: 99%